2019
DOI: 10.1029/2019jb017905
|View full text |Cite
|
Sign up to set email alerts
|

Grain Fragmentation and Frictional Melting During Initial Experimental Deformation and Implications for Seismic Slip at Shallow Depths

Abstract: During seismic slip, the elastic strain energy released by the wall rocks drives grain fragmentation and flash heating in the slipping zone, resulting in formation of (nano)powders and melt droplets, which lower the fault resistance. With progressive seismic slip, the frictional melt covers the slip surface and behaves as a lubricant reducing the coseismic fault strength. However, the processes associated to the transition from grain fragmentation to bulk frictional melting remain poorly understood. Here we di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 62 publications
3
11
0
Order By: Relevance
“…This peak stress corresponds to the shear stress strengthening stage due to incipient melt formation, which separates two stages of weakening observed in gabbro experiments (Hirose and Shimamoto, 2005). Similar shear stress evolution is observed at experiments with lower stress and slip rates, yet with one more stage of strengthening preceding the incipient melt formation due to a range of possible mechanisms (Hung et al, 2019). With higher heat production rates in natural fault zones at seismogenic conditions, we expect that there is only one stage of strengthening, which is much less pronounced than observed in experiments.…”
Section: Initial Conditions and Melt Transitionsupporting
confidence: 65%
See 2 more Smart Citations
“…This peak stress corresponds to the shear stress strengthening stage due to incipient melt formation, which separates two stages of weakening observed in gabbro experiments (Hirose and Shimamoto, 2005). Similar shear stress evolution is observed at experiments with lower stress and slip rates, yet with one more stage of strengthening preceding the incipient melt formation due to a range of possible mechanisms (Hung et al, 2019). With higher heat production rates in natural fault zones at seismogenic conditions, we expect that there is only one stage of strengthening, which is much less pronounced than observed in experiments.…”
Section: Initial Conditions and Melt Transitionsupporting
confidence: 65%
“…While the survivor clasts based on the imaged pseudotachylyte make up around 20% of the total volume, this fractional value is also variable during melting. Multiple stages slip experiments (Hung et al, 2019) show that the solid fraction evolves from 0.20 to 0.11 and returns to 0.20 at the final stage. For our simulations, we assume that the solid fraction is constant at 0.20 throughout the melting, and examine this assumption in the discussion.…”
Section: Temperature Dependence Of Viscositymentioning
confidence: 99%
See 1 more Smart Citation
“…Shear stress evolution with slip inferred from experiments performed on silicate‐built bare rocks, such as basalt and gabbro, is relatively well reproduced by the composite model made of flash heating and bulk melting, except of granitoid rocks for which the model yields the highest SNR values at low effective normal stress (≤10 MPa) (Figure S7 in Supporting Information S1). A possible explanation is that our viscosity model does not include the complexity of selective melting typical of frictional melting in granitoid rocks (Di Toro & Pennacchioni, 2004; Hung et al., 2019; Papa et al., 2021). Indeed, dedicated high‐velocity experiments using granitoid rocks showed that at low normal stresses (≤10 MPa) the compositional and structural evolution of the melt layer is extremely complex (Hung et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Motivating data are plotted with a linear time scale with inversions in the Supplement. (Reches and Lockner, 2010), grain fragmentation to weaker phases (Hung et al, 2019;Rattez and Veveakis, 2019), acoustic fluidization (Van der Elst et al, 2012), flash-heating (Goldsby and Tullis, 2011;Kitajima et al, 2011), frictional melt (Niemeijer et al, 2011), and/or other chemical processes (Violay et al, 2013). As the slip deficit is used up, fault slip must decelerate and friction will re-strengthen or heal (Violay et al, 2019), allowing seismologically-inferred self-healing pulsed slip behavior (Heaton, 1990) and larger dynamic than static stress drops (Brune, 1970).…”
Section: Introduction: Frictional Evolution Stages and Sliding Regimementioning
confidence: 99%